A PROSPECTIVE COHORT STUDY OF INTESTINAL OBSTRUCTION DUE TO TUBERCULOSIS. - Amit Kumar Gupta; Aditya Anand; Nawaz, Sarfaraz; Haider, Mohtamim (Student’s Journal of Health Research Africa, 2024)
Introduction Intestinal tuberculosis-related bowel obstruction is notably prevalent in underdeveloped nations. This study aims to explore the factors leading to suboptimal patient outcomes and to detail the surgical treatments, clinicopathological features, and prognoses of tuberculous intestinal obstruction in affected communities. Methods The prospective cohort study spanned 15 months at MGMMC & LSK Kishanganj, involving 123 patients treated surgically for tuberculous intestinal obstruction. Ethical approval was secured from the relevant authorities. Data analysis was performed using SPSS version 17.0, employing techniques such as descriptive statistics, chi-square tests for categorical data, and multivariate logistic regression to identify predictors of surgical outcomes. Results The study comprised 123 tuberculosis-related intestinal obstruction patients. Men outnumbered women 1.8 to 1. The median was 11–67 years old. The average age was 21–30. HIV-positive individuals had a median CD4+ count of 225 cells/μl, with 26.3% additionally having pulmonary tuberculosis. 58.5% of patients underwent emergency surgery, and 41.5% had elective surgeries. The most common operative findings were small bowel strictures (72.9%), followed by bands and adhesions (16.9%). An ileo-transverse anastomosis and right hemicolectomy were the most common surgeries at 55.9%. All patients received antituberculous drugs for a year after surgery. Surgical site infection (SSI) was the most common postoperative complication at 37.3% in 42.8%. HIV-positive status and low CD4+ count were the best predictors of SSI (p<0.001). Conclusion Tuberculous intestinal obstruction is highly prevalent and increases morbidity and mortality in the area, with patients often seeking help at advanced disease stages. Early diagnosis and effective treatment require heightened awareness, thorough evaluation, and proactive management. Recommendation Upon potential exposure to tuberculosis, it is critical to regularly monitor for symptoms, understand associated risks, and adhere to recommended preventative strategies.